Pré-processamento de modelo de veículo asmo para estudo de dinâmica de fluidos computacional - Lucena, Yzlla Rhavena (Universidade Federal Rural do Semi-Árido, 2019)
Computational fluid dynamics is a numerical simulation tool that has been gaining more and more space in industries in which the study of physical processes involving flows, involving the numerical solution of “Navier-Stokes equations”, is crucial. This advance has been driven by the recent evolution of the processing power of computers. However, many numerical challenges must be overcome to arrive at a computational fluids dynamic analysis that is accurate. This work addresses one of the main difficulties related to the threedimensional modeling of automotive vehicles in wind tunnels: the pre-processing of the mesh that represents the geometry of the vehicles. We started from a simple car model developed for didactic purposes by Daimler-Benz: the ASMO. Simplification and subdivision algorithms were applied, with the help of the free code software Meshlab, to adapt the mesh to the subsequent numerical solution of the flow equations by specialized software. It is demonstrated, from analysis of quality of the triangles that compose the mesh, that the processed mesh has a higher quality than the original model.
Artigo
Keywords: Dinâmica de fluidos computacional; Geração de malha; Triangulação; Túnel de vento; Computational fluid dynamics; Mesh generation; Triangulation; Wind tunnel; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA